A global Slc7a7 knockout mouse model demonstrates characteristic phenotypes of human lysinuric protein intolerance. (5th June 2020) - Stroup, Bridget M; Marom, Ronit; Li, Xiaohui; Hsu, Chih-Wei; Chang, Cheng-Yen; Truong, Luan D; Dawson, Brian; Grafe, Ingo; Chen, Yuqing; Jiang, Ming-Ming; Lanza, Denise; Green, Jennie Rose; et al.
Abstract: Lysinuric protein intolerance (LPI) is an inborn error of cationic amino acid (arginine, lysine, ornithine) transport caused by biallelic pathogenic variants in SLC7A7, which encodes the light subunit of the y + LAT1 transporter. Treatments for the complications of LPI, including growth failure, renal disease, pulmonary alveolar proteinosis, autoimmune disorders and osteoporosis, are limited. Given the early lethality of the only published global Slc7a7 knockout mouse model, a viable animal model to investigate global SLC7A7 deficiency is needed. Hence, we generated two mouse models with global Slc7a7 deficiency ( Slc7a7 em1Lbu/em1Lbu ; Slc7a7 Lbu/Lbu and Slc7a7 em1(IMPC)Bay/em1(IMPC)Bay ; Slc7a7 Bay/Bay ) using CRISPR/Cas9 technology by introducing a deletion of exons 3 and 4. Perinatal lethality was observed in Slc7a7 Lbu/Lbu and Slc7a7 Bay/Bay mice on the C57BL/6 and C57BL/6NJ inbred genetic backgrounds, respectively. We noted improved survival of Slc7a7 Lbu/Lbu mice on the 129 Sv/Ev × C57BL/6 F2 background, but postnatal growth failure occurred. Consistent with human LPI, these Slc7a7 Lbu/Lbu mice exhibited reduced plasma and increased urinary concentrations of the cationic amino acids. Histopathological assessment revealed loss of brush border and lipid vacuolation in the renal cortex of Slc7a7 Lbu/Lbu mice, which combined with aminoaciduria suggests proximal tubular dysfunction. Micro-computed tomography of L4 vertebrae and skeletal radiographs showed delayed skeletal development and suggested decreased mineralization in Slc7a7 Lbu/Lbu mice, respectively. In addition to delayed skeletal development and delayed development in the kidneys, the lungs and liver were observed based on histopathological assessment. Overall, our Slc7a7 Lbu/Lbu mouse model on the F2 mixed background recapitulates multiple human LPI phenotypes and may be useful for future studies of LPI pathology.